Nanoparticles With a Specific Size and Surface Charge Promote Disruption of the Secondary Structure and Amyloid-Like Fibrillation of Human Insulin Under Physiological Conditions - Sukhanova, Alyona; Poly, Simon; Bozrova, Svetlana; Lambert, Éléonore; Ewald, Maxime; Karaulov, Alexander; Molinari, Michael; Nabiev, Igor (Frontiers in Chemistry, 2019)
Nanoparticles attract much interest as fluorescent labels for diagnostic and therapeutic tools, although their applications are often hindered by size- and shape-dependent cytotoxicity. This cytotoxicity is related not only to the leak of toxic metals from nanoparticles into a biological solution, but also to molecular cytotoxicity effects determined by the formation of a protein corona, appearance of an altered protein conformation leading to exposure of cryptic epitopes and cooperative effects involved in the interaction of proteins and peptides with nanoparticles. In the last case, nanoparticles may serve, depending on their nature, as centers of self-association or fibrillation of proteins and peptides, provoking amyloid-like proteinopathies, or as inhibitors of self-association of proteins, or they can self-assemble on biopolymers as on templates. In this study, human insulin protein was used to analyze nanoparticle-induced proteinopathy in physiological conditions. It is known that human insulin may form amyloid fibers, but only under extreme experimental conditions (very low pH and high temperatures). Here, we have shown that QDs may induce amyloid-like fibrillation of human insulin under physiological conditions through a complex process strongly dependent on the size and surface charge of QDs. The insulin molecular structure and fibril morphology have been shown to be modified at different stages of its fibrillation, which has been proved by comparative analysis of the data obtained using circular dichroism, dynamic light scattering, amyloid-specific thioflavin T assay, transmission electron microscopy, and high-speed atomic force microscopy. We have found important roles of the QD size and surface charge in the destabilization of the insulin structure and the subsequent fibrillation. Remodeling of the insulin secondary structure accompanied by remarkable increase in the rate of formation of amyloid-like fibrils under physiologically normal conditions was observed when the protein was incubated with QDs of exact specific diameter coated with slightly negative specific polyethylene glycol (PEG) derivatives. Strongly negatively or slightly positively charged PEG-modified QDs of the same specific diameter or QDs of bigger or smaller diameters had no effect on insulin fibrillation. The observed effects pave the way to the control of amyloidosis proteinopathy by varying the nanoparticle size and surface charge.